Optimasi Sistem Irigasi Dengan Pendekatan Matematika Dan Pemodelan Hidrologi - Zalukhu, Cipri Agus Iman; Mendrofa, Elsa Greta; Zebua, Riki Arman; Mendrofa, Bicard Ridoan (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Efficient management of irrigation systems is crucial to enhance agricultural yields, especially in areas with limited water resources. This study aims to optimize irrigation systems using mathematical approaches and hydrological modeling. In this research, hydrological models are used to predict water availability, while mathematical methods are applied to determine the optimal water allocation to meet crop needs at the right time and in the appropriate amount. The results of this study can help design more efficient irrigation systems, reduce water waste, and improve agricultural sustainability. The application of this model can provide concrete solutions to address challenges posed by climate change and the management of increasingly limited water resources.